Conjunctive Administration of Intravenous Heparin Attenuates Cross-linked Fibrin Degradation in Patients Treated with Streptokinase - Galvani, Marcello; Abendschein, Dana R; Ferrini, Donatella; Ottani, Filippo; Rusticali, Franco; Eisenberg, Paul R (Thrombosis and Haemostasis, 1996)
Increases in thrombin activity occur in patients treated with streptokinase, but conjunctive therapy with intravenous heparin does not appear to improve either the rate of early infarct artery patency or survival in patients with acute myocardial infarction. In a recent study we found that concentrations of fibrinopeptide A, a marker of thrombin-mediated fibrin formation, were lower in the first 3 h in patients treated with intravenous heparin (5000 U bolus followed by a fixed-dose 1000 U/h infusion, n = 14) compared with subcutaneous (12,500 U every 12 h, started 4 h after streptokinase, n = 14) administration, but were increased in both groups of patients, consistent with persistent thrombin activity. To determine whether the differential effects of the intensity of heparinization on thrombin formation were reflected in differences in fibrin degradation, we measured cross-linked fibrin degradation products (XL-FDP) before and 1,2,3,8,12, and 24 h after streptokinase in the same cohort of patients, with a new ELISA with a D-dimer-specific capture antibody (MAb 3B6) and a fibrin-specific tag antibody (MAb 1D2, Agen, Brisbane, Australia). The incidence of early coronary recanalization assessed by creatine-kinase MM isoforms (increase in activity ≥0.18%/min), was similar in both groups (79 vs 86%). Concentrations of XL-FDP were similar in patients with and without recanalization, but were lower in patients treated with intravenous compared with subcutaneous heparin at 8 h, but the results did not reach statistical significance (627 ±151 ng/ml versus 1007 ± 157 ng/ ml, p = 0.06), and were significantly lower at 12 h (327 ± 72 versus 781 ± 162 ng/ml, p = 0.03 at 12 h) (mean ± SEM). Concentrations of cross-linked fibrin degradation products were also lower in patients in whom the activated partial thromboplastin time was greater than two times the control, compared with those with inadequate anticoagulation (498 ± 105 versus 1084 ± 179 ng/ml; p = 0.02) (mean ± SEM). Thus, more effective inhibition of thrombin with conjunctive intravenous heparin therapy results in less cross-linked fibrin turnover in the first 12 h after thrombolysis with streptokinase. This probably reflects decreased fibrin formation with therapeutic anticoagulation.